Test of JYUTube as a veto detector at MARA for background suppression in nuclear spectroscopy beyond the proton drip line - Sottili, Leandro (2018)
At JYFL-ACCLAB a Mass Analysing Recoil Apparatus (MARA) was built to per- form nuclear spectroscopy of exotic nuclei with N=Z in the region A∼80 created via fusion evaporation reactions at low energies (3-6 MeV/u). Fusion recoils are collected with a detector system placed on the focal plane of MARA. A limit of this technique is the presence of unwanted masses/isobars, created in the reactions, that reach the focal plane. One way to reduce this source of background is to use a detector as a veto at the target position to select and to exclude at the focal plane the unwanted products. For this purpose JYUTube was installed at MARA and tested with the 78 Kr+ 96 Mo → 174 Pt ∗ reaction. In this test, the JYUTube showed an efficiency of 65% for 1 proton channel suppression and 80% for 2 protons channel suppression.